Protection of the Right to Life - Villavicencio Terreros, Felipe (2015)
In this paper the author discusses about protecting the right to life. However, what is problematic generates at what point originates or begins to human life and when this ends. Criminal Law For life is a biopsychosocial phenomenon inseparably social and dynamic. Also, to be dynamic, you can not assert the existence of an exact point of when life begins. Thus, the right to life has a complex nature to be the foundation of all other legal rights, without which no other rights have any existence. While the limits of the protection of the right to life are discussed, the author considers it appropriate in the present approach the nesting of the fertilized egg in the uterus as minimum limit this right. Furthermore, it is the issue of when human life ends. Criminal law maintains protection of the right to life of the person until the end with the death of the person. While the concept of death has varied over time, currently with the medical - legal is guided by the General Health Law that